Realia funkcjonowania grup poszukiwawczo-ratowniczych w Polsce - Mencel, Patrycja (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The disappearance of a person is an event that demands coordination of the enti-ties involved in the search for missing persons. Cooperation of governmental search and rescue services with other entities specializing in search operations is of great importance in the system of locating missing persons, as it increases the chances of saving the life of a lost person.
Keywords: zaginięcie osoby; poszukiwanie; współpraca